2004
DOI: 10.1074/jbc.m400731200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced Recruitment of the Secretory Vesicle Protein DOC2B to the Target Membrane

Abstract: Ca 2؉ -dependent fusion of transport vesicles at their target can be enhanced by intracellular Ca 2؉ and diacylglycerol. Diacylglycerol induces translocation of the vesicle priming factor Munc13 and association of the secretory vesicle protein DOC2B to the membrane. Here we demonstrate that a rise in intracellular Ca 2؉ is sufficient for a Munc13-independent recruitment of DOC2B to the target membrane. This novel mechanism occurred readily in the absence of Munc13 and was not influenced by DOC2B mutations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 27 publications
(47 reference statements)
3
51
1
Order By: Relevance
“…However, two key findings presented here suggest a novel role for Doc2␤ function in endocrine cell exocytosis: 1) Munc18c does not bind the C2A domain of Doc2␤, but rather binds to the C2B domain instead; 2) Doc2␤ localized principally to the plasma membrane fractions in both islet beta cells and 3T3L1 adipocytes. Moreover, in PC12 and chromaffin cells Doc2␤ on vesicles translocates to the plasma membrane upon Ca 2ϩ stimulation to facilitate vesicle priming (32,(43)(44)(45). In contrast, we did not observe this translocation event in MIN6 beta cells, a cell type well known to elicit insulin exocytosis in response to Ca 2ϩ stimulation.…”
Section: Discussioncontrasting
confidence: 45%
“…However, two key findings presented here suggest a novel role for Doc2␤ function in endocrine cell exocytosis: 1) Munc18c does not bind the C2A domain of Doc2␤, but rather binds to the C2B domain instead; 2) Doc2␤ localized principally to the plasma membrane fractions in both islet beta cells and 3T3L1 adipocytes. Moreover, in PC12 and chromaffin cells Doc2␤ on vesicles translocates to the plasma membrane upon Ca 2ϩ stimulation to facilitate vesicle priming (32,(43)(44)(45). In contrast, we did not observe this translocation event in MIN6 beta cells, a cell type well known to elicit insulin exocytosis in response to Ca 2ϩ stimulation.…”
Section: Discussioncontrasting
confidence: 45%
“…While the requirement of Ca 2C for Rip11 binding to acidic phospholipids has yet to be determined, in adrenal chromaffin cells, Doc2b is recruited to the cell surface in a Ca 2C -dependent manner where it functions as a priming factor and increases the number of fusion-competent vesicles (Groffen et al 2004, Friedrich et al 2008. A recent study in 3T3-L1 adipocytes has demonstrated that Doc2b is recruited to the plasma membrane in an insulinand Ca 2C -dependent manner where it associates with syntaxin4 (Fukuda et al 2009).…”
Section: Protein Complexes Involved In Docking and Fusion Of Glut4 Vementioning
confidence: 99%
“…2+ measurements and DOC2B translocation in PC12 cells Constructs encoding DOC2B domains C2A (residues 125-255), C2B (residues 265-412), and C2AB (residues 125-412), all fused to eGFP, were created by deletion of relevant coding regions from a DOC2B-eGFP (N2) plasmid [51] using a standard QuikChange mutagenesis protocol. PC12 cells overexpressing the C2A, C2B, C2AB, or the full-length protein were pre-incubated with a serum-free medium (Opti-MEM; Gibco) for 2 h at 37°C.…”
Section: Combined Camentioning
confidence: 99%